2014
DOI: 10.2174/1745017901410010028
|View full text |Cite
|
Sign up to set email alerts
|

“Nomophobia”: Impact of Cell Phone Use Interfering with Symptoms and Emotions of Individuals with Panic Disorder Compared with a Control Group

Abstract: Panic disorder refers to the frequent and recurring acute attacks of anxiety. Objective: This study describes the routine use of mobiles phones (MPs) and investigates the appearance of possible emotional alterations or symptoms related to their use in patients with panic disorder (PD). Background: We compared patients with PD and agoraphobia being treated at the Panic and Respiration Laboratory of The Institute of Psychiatry, Federal University of Rio de Janeiro, Brazil, to a control group of healthy volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
155
0
28

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 244 publications
(187 citation statements)
references
References 12 publications
4
155
0
28
Order By: Relevance
“…Panic disorder indicates frequent and constant anxiety attacks. In a study conducted by King et al (2014) in Brazil, the symptoms and mood changes of patients with panic disorder due to mobile phone usage were examined. A total of 120 people participated in this experimental study and it was found that both the experimental group (with panic disorder) and the control group (reported as healthy) showed dependence on mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…Panic disorder indicates frequent and constant anxiety attacks. In a study conducted by King et al (2014) in Brazil, the symptoms and mood changes of patients with panic disorder due to mobile phone usage were examined. A total of 120 people participated in this experimental study and it was found that both the experimental group (with panic disorder) and the control group (reported as healthy) showed dependence on mobile phones.…”
Section: Introductionmentioning
confidence: 99%
“…Personal resilience, a positive characteristic, was significantly and positively correlated with affinity for the mobile phone for Productivity purposes and negatively correlated with both negative subscales. This finding differentiates the MPAS from other instruments in that both impulsivity and anxiety have been shown to be associated with mobile phone use in studies of mobile phone addiction or dependence [39-41]. However, the Connectedness subscale was not correlated with resilience, which is reasonable given that personal relationships with others can help promote personal resilience [42,43], but can also place a burden on individuals [44].…”
Section: Discussionmentioning
confidence: 81%
“…King et al [1] has offered as a diagnostic category the disorder of pathologic dependence of the CITC for those individuals for which the abusive use of the referred technologies should be associated to a primary mental disorder with losses to the personal, social, familial and professional aspects and the involvement of the quality of the individuals' life [18][19][20].…”
Section: Resultsmentioning
confidence: 99%